2019
DOI: 10.1038/s41598-019-47910-1
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic PD-L1 antibodies are more effective than PD-1 antibodies in blocking PD-1/PD-L1 signaling

Abstract: Inhibitors of PD-1 signaling have revolutionized cancer therapy. PD-1 and PD-L1 antibodies have been approved for the treatment of cancer. To date, therapeutic PD-1 inhibitors have not been compared in a functional assay. We used an efficient T cell reporter platform to evaluate the efficacy of five clinically used PD-1 inhibitors to block PD-1 signaling. The half maximal effective concentrations (EC 50 ) for nivolumab and pembrolizumab were 76.17 ng/ml (95% CI 64.95–89.34 ng/ml) and 39.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(106 citation statements)
references
References 33 publications
(43 reference statements)
2
102
1
1
Order By: Relevance
“…Recent in vitro studies suggest that differences between receptor- vs. ligand-based antagonism may exist and have implications for combination treatments. In a study using a functional T-cell in vitro assay, PD-L1 antibodies were found to be more effective than PD-1 antibodies in inhibiting PD-1 signaling ( 215 ). A study using in vivo murine breast and colon cancer models showed that anti–PD-L1 (but not anti–PD-1) monotherapy was able to deplete CD80 ligand expression on tumor-infiltrating antigen-presenting cells, thereby inhibiting CTLA-4 axis through a Treg-dependent mechanism ( 216 ).…”
Section: Challenges and Future Opportunities: Where Do We Go From Hermentioning
confidence: 99%
“…Recent in vitro studies suggest that differences between receptor- vs. ligand-based antagonism may exist and have implications for combination treatments. In a study using a functional T-cell in vitro assay, PD-L1 antibodies were found to be more effective than PD-1 antibodies in inhibiting PD-1 signaling ( 215 ). A study using in vivo murine breast and colon cancer models showed that anti–PD-L1 (but not anti–PD-1) monotherapy was able to deplete CD80 ligand expression on tumor-infiltrating antigen-presenting cells, thereby inhibiting CTLA-4 axis through a Treg-dependent mechanism ( 216 ).…”
Section: Challenges and Future Opportunities: Where Do We Go From Hermentioning
confidence: 99%
“…As tumour-targeting probes, we used four types of monoclonal antibodies such as anti-HER2 antibody (Herceptin), 20 anti-EGFR antibody (Erbitux), 21 anti-VEGFR-2 antibody (Cyramza), 22 and anti-PD-L1 antibody (anti-PD-L1 ab). 23 These monoclonal antibodies are used as antibody drugs of cancer therapy for breast and skin tumours in clinical elds. By using the ICG-antibody conjugates, we conducted NIR and SWIR uorescence imaging of breast and skin tumours in mice.…”
Section: Introductionmentioning
confidence: 99%
“…In some experiments, cells were pretreated with different antibodies or proteins like CD71 mAbs (5 µg/ml), transferrin (50 µg/ml), Abraxane (100 ng/ml), HSA or HSA-heme (both 200 µg/ml). K D value for HSA-heme was calculated as described 61 . Flow cytometry analyses were performed using FACSCalibur flow cytometer (Becton Dickinson, Franklin Lakes, NJ).…”
Section: Methodsmentioning
confidence: 99%